Climate Change Instrument Through Green Taxation in Achieving Environmental Sustainability - Sari, Sinta Puspita; Srihastuti, Eni; Niam, Muhammad Alfa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Climate change remains a critical global challenge requiring effective policy interventions. Green taxation has emerged as a strategic policy instrument to mitigate environmental degradation and promote sustainability. This study investigates the impact of green taxes on environmental sustainability, particularly in energy sector companies disclosing carbon emissions from their operations. Additionally, it examines the role of Environmental, Social, and Governance (ESG) disclosures in fostering sustainable practices. A quantitative approach is employed, using purposive sampling to select a sample of energy sector companies listed on the Indonesia Stock Exchange (BEI) between 2022 and 2023. The sample criteria include: (1) energy companies listed on the BEI, (2) non-top-listed firms during the same period, and (3) firms without a complete sustainability report, resulting in 68 data points. This study utilizes secondary data sourced from company annual reports, analyzed using SPSS V25 software. The findings reveal that green taxes exert a significant and positive influence on environmental sustainability. The study’s results are expected to contribute to the formulation of more effective environmental policies in Indonesia, while also advocating public awareness and support for green tax implementation through structured socialization efforts.